Penilaian Kualitas Informasi Laporan Keuangan Kuasa BUN Daerah: Studi KPPN Wilayah Maluku - Aryo Budiwidarto; Iskandar Iskandar (Polytechnic of State Finance STAN, 2022)
This study explores the methods, criteria, and results of assessing the quality of information reflected in the financial report. The research method used is the study of literature, documentation, and observation, with the object of studying the assessment of LK KBUN-D KPPN in Maluku Province. The research results show that the assessment criteria have considered the elements (characteristics) in assessing the quality of information. The results of the LK KBUN-D information quality assessment have achieved a very high score on all assessment criteria. The value of the information quality of LK KBUN-D for all KPPN in the Maluku region on the criteria of timeliness, data accuracy, and completeness of documents received full marks. For the participation criteria, the results of reconciliation with the spending units still found data/transactions that were not normal, but in relatively small amounts. These results provide an overview of the quality assessment of LK, and recommendations for improvement. Keywords: Information Quality, Financial Report, Accuracy, Assessment, State Treasurer